Optimum design for the ballistic diode based on graphene field-effect transistors - Van Huy Nguyen (Nature Portfolio, 2021)
Abstract We investigate the transport behavior of two-terminal graphene ballistic devices with bias voltages up to a few volts suitable for electronics applications. Four graphene devices based ballistic designs, specially fabricated from mechanically exfoliated graphene encapsulated by hexagonal boron nitride, exhibit strong nonlinear I-V characteristic curves at room temperature. A maximum asymmetry ratio of 1.58 is achieved at a current of 60 µA at room temperature through the ballistic behavior is limited by the thermal effect at higher bias. An analytical model using a specular reflection mechanism of particles is demonstrated to simulate the specular reflection of carriers from graphene edges in the ballistic regime. The overall trend of the asymmetry ratio depending on the geometry fits reasonably with the analytical model.